Minority Marketing: Research Perspectives for the 1990s Proceedings of the 1993 Minority Marketing Congress - King, Robert L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume includes the full proceedings from the 1993 Minority Marketing Congress held in Long Beach, Mississippi under the theme Minority Marketing: Research Perspectives for the 1990s. It provides a variety of quality research in the field of minority marketing in order to assimilate and enhance knowledge of marketing practices for minority enterprises. It includes papers on various topics in minority marketing including advertising, promotion and consumer behavior. Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy’s flagship journals, the Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science.
Foreword -- Preface -- Marketing Strategies for Reaching Minority Markets -- Redefining Ethnic Market Segmentation -- An Assessment of the Impact of Racially Homogeneous Reference Groups on Strength of Ethnic Affiliation for Black Customers -- Initial Impressions in the Retail Buyer-Seller Dyad -- The Effects of Ethnicity and Income on the Reported Importance of Selected Retail  Store Evaluative Criteria -- Promoting to Minorities -- Media Usage and the Buying Behavior of Hispanics -- The Impact of Promotional Offers on the African American Customer -- Uptown Cigarettes -- An Empirical Investigation of the Impact of Viewers’ Race on their Association of Celebrities in Television Advertising -- An Analysis of Frequency Portrayal of Minority Models in Magazine Advertisements -- A Selected Bibliography on Marketing to African Americans and Hispanics Since the Late 1970s -- The Effect of Ethnic Acculturation on Advertising Perceptions -- Segmenting the Asian American Consumer Market -- Marketing Strategies for Asian-Americans -- Three Additional Factors of Native, American Purchase Behavior -- An Examination of the Ethical Dispensation of Health Care in the United States -- Employment Status as a Basis of Segmentation of Female Consumers’ Adaptive Shopping Behavior -- Societal Influences on Schematic Processing in the Service Encounter -- Marketing Credit/Mortgage Services in Under Served Markets -- Business Social Responsibility -- Trends and Strategies in the Marketing of Corporate Image and Identify in a Politically-Conscious South Africa.
Keywords: Marketing; Leadership; Sales management; Marketing; Business Strategy/Leadership.; Sales/Distribution.